2014
DOI: 10.11646/phytotaxa.175.1.6
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Paraphlomis (Lamiaceae) from Korea: an additional genus to the Korean flora

Abstract: A new species, Paraphlomis koreana S.C.Ko et G.Y.Chung, from Korea is described and illustrated. The species is similar to P. albida Hand.-Mazz. in general vegetative characters and white corollas, but the new species is distinguished by its smaller stature, equally toothed 10-veined calyces, and pink-spotted lower corolla lips. P. koreana S.C.Ko et G.Y.Chung has been only found in Bogil-do Island, a small island in the Southern Ocean of Korea, and is the first species described from the genus in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Paraphlomis (Prain) Prain is a member of the tribe Paraphlomideae Bendiksby (Lamiaceae, Lamioideae) (Bendiksby et al 2011;Li et al 2016;Zhao et al 2021). Most species of Paraphlomis are distributed in southern China, with several species occurring in the Himalayas, Korea and Southeast Asia (Li and Hedge 1994;Wu and Li 1997;Ko et al 2014;Chen et al 2021). Previous molecular phylogenetic studies of Paraphlomis revealed that the genus was not monophyletic, because species of Matsumurella were recovered within it (Chen et al 2021;Chen et al 2022b;Guo et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraphlomis (Prain) Prain is a member of the tribe Paraphlomideae Bendiksby (Lamiaceae, Lamioideae) (Bendiksby et al 2011;Li et al 2016;Zhao et al 2021). Most species of Paraphlomis are distributed in southern China, with several species occurring in the Himalayas, Korea and Southeast Asia (Li and Hedge 1994;Wu and Li 1997;Ko et al 2014;Chen et al 2021). Previous molecular phylogenetic studies of Paraphlomis revealed that the genus was not monophyletic, because species of Matsumurella were recovered within it (Chen et al 2021;Chen et al 2022b;Guo et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Previous molecular phylogenetic studies of Paraphlomis revealed that the genus was not monophyletic, because species of Matsumurella were recovered within it (Chen et al 2021;Chen et al 2022b;Guo et al 2023). In general, Paraphlomis is characterized by its herbaceous habit, actinomorphic calyx with five lobes less than half as long as the tube, corolla 2-lipped (1/3) with hairy upper lip but hardly bearded along the margin, included stamens and an apically truncate ovary (Wu and Li 1977;Bendiksby et al 2011;Ko et al 2014;Chen et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a member of tribe Paraphlomideae ( Lamiaceae , Lamioideae ) ( Bendiksby et al 2011 ; Zhao et al 2021 ), the genus Paraphlomis Prain is characterised by its herbaceous habit, actinomorphic calyx with five lobes less than half as long as the tube, corolla 2-lipped (1/3) with hairy upper lip, but hardly bearded along the margin, included stamens and an apically truncate ovary ( Wu and Li 1977 ; Bendiksby et al 2011 ; Chen et al 2021 ). A total of 36 species and seven varieties are recognised within Paraphlomis , most of which are distributed in southern China ( Chen et al 2022b ; Yuan et al 2022 ), with several species occurring in the Himalayas, Korea and Southeast Asia ( Li and Hedge 1994 ; Ko et al 2014 ; Chen et al 2021 ). Many species of Paraphlomis are endemics of limestone soils, including the recently described P. kuankuoshuiensis R.B.…”
Section: Introductionmentioning
confidence: 99%
“… Paraphlomis (Prain) Prain, a member of the tribe Paraphlomideae Bendiksby ( Lamiaceae : Lamioideae ) ( Bendiksby et al 2011 ; Li et al 2016 ; Zhao et al 2021 ), is characterized by its herbaceous habit, actinomorphic calyx with five lobes less than half as long as the tube, corolla 2-lipped (1/3) with hairy upper lip but hardly bearded along the margin, included stamens and an apically truncate ovary ( Wu and Li 1977 ; Bendiksby et al 2011 ; Ko et al 2014 ; Chen et al 2021 ). Paraphlomis is endemic to eastern and southeastern Asia, including China, India, Indonesia, Korea, Laos, Myanmar, Thailand, and Vietnam ( Li and Hedge 1994 ; Ko et al 2014 ; Zhang et al 2020 ; Chen et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%